A characterisation of common bottlenose dolphin (Tursiops truncatus) interactions with the commercial shrimp trawl fishery of South Carolina, USA - Greenman, Justin T.; Mcfee, Wayne E. (J. Cetacean Res. Manage., 2023)
In the United States, interactions between the shrimp trawl fishery and bottlenose dolphins are known to exist; however, the level of mortality is largely unknown, and has not been studied in South Carolina, USA. The current study attempted to determine if interactions between bottlenose dolphins and the South Carolina commercial shrimp trawl fishery pose a significant threat to dolphin populations and if fishery related mortality is underreported. Onboard observations were made during a 25 day (August–December 2010) field study. No dolphin takes occurred during the observational period. These observations focused on direct physical interactions with the gear and depredation behaviours. Additionally, a subsample of the shrimp fishery in South Carolina was asked to participate in a mailed survey. The survey included questions related to gear, dolphin observations, and the status of the shrimp fishery. This paper also examines historical dolphin stranding data from the NOAA/CCEHBR MMIS database for signs of shrimp fishery interactions. A three-tiered flow diagram was developed to characterise each stranding case according to the likelihood that mortality resulted from trawler interaction. Field results point to significant dolphin presence around commercial trawlers (x2 = 23.406, p < 0.001). Survey results showed 12 unreported incidents of shrimp trawl fishery mortality of dolphins. Finally, stranding records revealed several more cases with signs of possible trawler interaction. The current US National Marine Fisheries Service (NOAA) designation of the fishery as a Category II fishery is correct. Increased observer coverage and improved communication with the fishery on the importance of reporting takes is warranted.